Effect of air flow rate on the emission of burning coconut shell for biofuel product - Hazman, Nurhazwani; Mat Isa, Norasikin; Nasir, Nurul Fitriah; Mohd Yunos, Siti Nur Mariani (TRKU, 2020)
The increasing awareness of the depletion of fossil fuel resources and their bad impact towards environmental lead to an application of biofuel as alternative choice. The production of biofuel from waste offers a triplet-facet solution includes economic, environmental and waste management. In the present study, the use of biofuel that most abundantly available for power generation is applicable in the form of waste. Coconuts are the abundant renewable resource of energy can be found in all around the world especially Southeast Asia like Malaysia, Indonesia and Philippines. In this study, the waste of coconut shell was prepared to become a biofuel in form of powder or pulverized. The sample was undergo burning process at five different air flow rate that been set up. The effect of burning pulverized coconut shell on environmental impact was studied from CO2 and CO emission. The influence of air flow rate on ash properties were studied using SEM image and EDX analysis. The results revealed that microstructure of coconut shell ash are irregular, asymmetrical, disperse and non-overlap compare to coal. The influence of air flow rate of primary gave effect on the CO2 and CO emission. As the air flow rate increased, the weight of carbon fly ash increases while oxygen experiencing the decreases. In addition, the existed elements such as C, O, Mg, Fe and Ni for each cases were determined. It was also found that the coconut shell is lower in ash content, it tends to produce less particulates and has almost no Sulphur oxides compare to coal. At the end of this work, research would like to recommend use of coconut shell as an additive material in heat generation as it is not containing harmful ash content.